Review on multi-input DC-DC converters topologies for electric vehicle charging application - Rajalakshmi, M.; Sultana, W. Razia; Vanishree, J.; Chitra, A.; Prabha, D. Rama; Manimozhi, M. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The evolving fast-charging technology ends the hindrances of electric vehicle (EV) usage by integrating renewable energy sources and hybrid energy storage systems to increase the range and reliability of the vehicle. Nowadays, the development of the smart grid hosts bi-directional operation for improving the power quality by sending power from EV to the grid. For that, the multi-input (MI) converters are the breakthrough with the bidirectional conduction operation, which supports the power flow from vehicle to grid, vehicle, and building operation (V2X). Another important criterion for EV chargers is the high-power density with less losses by zero voltage and current switching and less circulating current, which can be achieved with resonant converters. All existing reviews missed out on focusing on resonant converters for bi-directional MI converters. This paper reviews the bi-directional converter topologies with multiple inputs suitable for V2X operation based on high and low voltage, frequency, control, and switching components.